127k views
5 votes
Solve for y.

–5(y − 3) − 10 = –6y

y =

User Statmaster
by
5.0k points

2 Answers

2 votes

Answer:

y = -5

Explanation:

–5(y − 3) − 10 = –6y

First, open up the brackets.

-5y + 15 - 10 = -6y

-5y + 5 = -6y

Move y to the same side. ( when you move the numbers to the opposite side , be aware of changing the negatives and positives )

-5y + 6y = -5

y = -5

User Jonnystoten
by
5.2k points
5 votes

Answer:

y = - 5

Explanation:

–5(y − 3) − 10 = -6y

-5y + 15 - 10 = -6y

-5y + 5 = -6y

5 = - 6y + 5y

5 = -y

-5 = y

User MsBugKiller
by
4.7k points